(untitled) (Research, Society and Development, 2021)
The Itapecuru River has undergone intense processes of environmental degradation, due to some irregular interference of anthropic actions, as well as decline of riparian vegetation, among other actions that are causing damage to the environment and the health of the population that uses this water for various purposes such as: bathing, fishing activities, irrigation plants among others. This work was developed with the aim of analyzing the physical-chemical parameters of the water quality of the Itapecuru River in the municipality of Caxias-MA. It was a study of experimental nature, with quanti-qualitative approach, performed in the period from July 22 to September 8, 2021. The collections were obtained in 10 points. The parameters analyzed were: water temperature, electrical conductivity, hydrogen potential (pH) and dissolved oxygen (O.D.). The average temperature of the points was 26.8 ºC. The highest mean conductivity was 60.57 µS/cm and the lowest mean was 32.47 µS/cm. In the hydrogen potential, the highest average was 7.6 and the lowest was 6.7. Regarding dissolved oxygen, the highest average was 10.47 mg/L and the lowest average was 5.23 mg/L. According to the data obtained in this research the temperature showed values above the limit allowed for Class 2 according to the National Program for the Evaluation of Water Quality (PNQA) and the conductivity, pH and O.D. parameters were within the standards of the current legislation.